2016
DOI: 10.1177/1971400916665376
|View full text |Cite
|
Sign up to set email alerts
|

Accuracy of SWI sequences compared to T2*-weighted gradient echo sequences in the detection of cerebral cavernous malformations in the familial form

Abstract: The SWI sequence, being more sensitive to substances which distort the local magnetic field than the GRE T2*W sequence, showed a higher sensitivity in identifying cerebral cavernous malformations. Thus, routine clinical neuroimaging protocol should contain SWI sequences to evaluate patients with (or suspected) cerebral cavernous malformations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 31 publications
(21 citation statements)
references
References 22 publications
1
17
0
2
Order By: Relevance
“…The SWI sequences were obtained using a technique that combines a long-TE high-resolution fully flow-compensated 3DGRE sequence with filtered phase information in each voxel both to enhance the contrast in magnitude images and add the susceptibility differences between tissues as a new source of information. [15][16][17][18] The SWI images were obtained without the injection of contrast material (TR/TE, 34/24; flip angle 10 ; FOV 22 cm; matrix 256 Â 512; slice thickness 1.2 mm; no intersection gap; number of images 140; number of excitations 1; and acquisition time 5.40 minutes). The SWI images were also post-processed with the minimum intensity projection (MinIP) algorithm in the axial plane with a slice thickness of 3-10 mm to visualize better the 'signal void' of the vessel structures.…”
Section: Mri Protocolmentioning
confidence: 99%
“…The SWI sequences were obtained using a technique that combines a long-TE high-resolution fully flow-compensated 3DGRE sequence with filtered phase information in each voxel both to enhance the contrast in magnitude images and add the susceptibility differences between tissues as a new source of information. [15][16][17][18] The SWI images were obtained without the injection of contrast material (TR/TE, 34/24; flip angle 10 ; FOV 22 cm; matrix 256 Â 512; slice thickness 1.2 mm; no intersection gap; number of images 140; number of excitations 1; and acquisition time 5.40 minutes). The SWI images were also post-processed with the minimum intensity projection (MinIP) algorithm in the axial plane with a slice thickness of 3-10 mm to visualize better the 'signal void' of the vessel structures.…”
Section: Mri Protocolmentioning
confidence: 99%
“…The SWI sequence is a velocity compensated highresolution 3D gradient-echo sequence that uses magnitude and filtered-phase information to create a new contrast. [9][10][11] As a result, CMBs are more sensitively detected by SWI compared with T2*-weighted GRE. 3,[12][13][14] A previous study 4 based on 3 T MR imaging and T2* GRE sequence demonstrated an association between lobar distributed CMBs and cerebrospinal fluid (CSF) amyloid-beta (A) levels as well as with CSF phosphorylated tau 181 protein (p-tau) levels and the presence of cognitive decline in AD patients.…”
Section: Introductionmentioning
confidence: 87%
“…As a result, CMBs are more sensitively detected by SWI compared to T2*-weighted GRE [3,8,[11][12][13][14].…”
Section: Introductionmentioning
confidence: 93%
“…In recent years, with the introduction of susceptibilityweighted imaging sequences, and with the wider availability of 3T MR units, there was an increased sensitivity of detection of small cerebral microbleeds [7,8,19].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation